Clinical characteristics and prognoses of pulmonary mucormycosis in four children - Siyuan Guo; Hui Liu; Xiaolei Tang; Haiming Yang (Wiley, 2019)
Abstract Importance Pulmonary mucormycosis is life threatening and carries a poor prognosis. Identification of factors that improve prognosis is urgently necessary. Objective To analyze the clinical features and outcomes of pulmonary mucormycosis in children. Methods A retrospective analysis of clinical data of four cases with pulmonary mucormycosis was conducted in Beijing Children's Hospital from January 2017 to December 2018. Results Underlying diseases were identified in all four cases (diabetes in three individuals and a hematological malignancy in one individual). The predominant clinical manifestations were fever, cough, chest pain and hemoptysis. Imaging features included consolidation or nodules with cavities. All four cases were treated with liposomal amphotericin B, one case underwent lobectomy, and three cases received a full course of posaconazole. All four cases were cured. Interpretation Patients with pulmonary mucormycosis often have underlying diseases. Imaging features are relatively characteristic. Treatment with liposomal amphotericin B at an early stage and a sufficient course of posaconazole for maintenance significantly improves prognosis.